Relatedness Need Satisfaction and the Dark Triad: The Role of Depression and Prevention Focus - Xiao, Mengqi; Wang, Zhuofan; Kong, Xiaoshan; Ao, Xiya; Song, Jia; Zhang, Peng (Frontiers in Psychology, 2021)
Dark Triad traits are often associated with maladaptive social and interpersonal interactions, such as dishonesty and self-centeredness, thus it is important to explore predictors of the Dark Triad in order to better facilitate the reduction of such behaviors. The present study adopted a self-report approach with a total of 5,207 Chinese undergraduate students participated in the study. We found that relatedness need dissatisfaction significantly predicted the presence of dark personalities, which was mediated by prevention focus. Conditional process model analysis found that this mediating effect was stronger when depression levels were lower. Final study results contributed to further understanding predictors of the Dark Triad. Study limitations and future research directions were also examined.